Perception of unemployment in a group of middle-class families emergent - Caballero Colonia, Leticia Kathery (2020)
The present work is of a qualitative nature that aims to know the perception of unemployment as a result of the implications of the health emergency situation caused by Covid 19, semi-structured interviews were carried out with a group of unemployed young people from the Puente Piedra district - Las Orquídeas Association - stage 1, located next to one of the largest markets in Lima - North, Mercado Huamantanga.